Annotated records of scombroid eggs and larvae distribution in northeastern Mediterranean waters - VASSILOPOULOU, V.; SIAPATIS, A.; PAPACONSTANTINOU, C.; CARAGITSOU, E. (Mediterranean Marine Science, 2008)
The distribution of eggs and larvae of scombroid fish in northeastern Greek waters were studied during the summer of three consecutive years(1992-1994) to determine spawning, time of spawning peaks, and the possible preferred spawning grounds. Among eggs only those of Xiphias gladius were successfully identified. Larvae of Thunnus alalunga, Euthynnus alleteratus, X. gladius and Auxis rochei were recorded, the latter species being encountered more frequently than the rest. Most scombroid larvae were collected in the Sporades Islands’ basin and their abundance, particularly that of A. rochei, was relatively increased at the end of the summer, possibly suggesting increased spawning activities during that period.